Efficacy of a global supportive skin care programme with hydrotherapy after non‐metastatic breast cancer treatment: A randomised, controlled study. (22nd August 2017) - Dalenc, F.; Ribet, V.; Rossi, A.B.; Guyonnaud, J.; Bernard‐Marty, C.; de Lafontan, B.; Salas, S.; Ranc Royo, A.‐L.; Sarda, C.; Levasseur, N.; Massabeau, C.; Levecq, J.‐M.; et al.
Abstract : This study investigated the efficacy of post‐treatment hydrotherapy as supportive care for management of persistent/long‐lasting dermatologic adverse events (dAEs) induced in breast cancer survivors by adjuvant therapy, and its impact on quality of life (QoL). Patients in complete remission after standardised (neo)adjuvant chemotherapy, surgery and radiotherapy combination treatment for infiltrating HR+/HER2‐breast carcinoma were enrolled in this randomised, multicentre controlled study 1–5 weeks after completing radiotherapy. The control group (CG, n  = 33) received best supportive care and the treatment group (HG, n  = 35) received 3‐weeks of specific hydrotherapy. The primary criterion was change in QoL (QLQ‐BR23) after hydrotherapy. Clinical grading of dAEs, cancer‐related QoL (QLQ‐C30), dermatologic QoL (DLQI) and general psychological well‐being (PGWBI) were assessed. Significant dAEs were found at inclusion in both groups ( n  = 261). Most items showed significantly greater improvement in the HG versus CG group: QLQ‐BR23 (breast [ p  = .0001] and arm symptoms [ p  = .0015], systemic therapy side effects [ p  = .0044], body image [ p  = .0139]), some dAE grading, DLQI ( p  = .0002) and PGWBI ( p  = .0028). Xerosis (88% of patients at inclusion) completely healed in all HG patients. Specific hydrotherapy is an effective supportive care for highly prevalent and long‐lasting dAEs occurring after early breast cancer treatment, including chemotherapy, and leads to improved QoL and dermatologic toxicities.